Engagement in Daily Life Activities of Adults Ageing with an Intellectual Disability - KING, EILISH (Trinity College Dublin. School of Nursing & Midwifery. Discipline of Nursing, 2018)
Background: Occupational therapists view engagement in meaningful activities to be a key determinant of health and well-being. As the population of people ageing with an intellectual disability (ID) continues to grow, strategies to enable this population to continue to actively engage in daily life need to be explored in order to support successful ageing for this population. Aims: This study aimed to examine engagement of adults ageing with an intellectual disability in daily life activities, and to identify factors that influence engagement in daily life using objectively measurable data. Methods: Data from wave two of the Intellectual Disability Supplement to the Irish Longitudinal Study on Ageing (IDS-TILDA) was analysed in order to identify predictors of engagement in self-care, productivity and leisure activities of adults ageing with intellectual disabilities. A modified occupational perspective was used, which considered key indicators of personal, environmental and activity factors that may influence engagement in daily life activities. Logistic and linear regression techniques were used in order to identify predictors of engagement. Findings: Difficulty getting around the physical environment of the home and local community was identified as the strongest predictor of preclusion from engagement in daily life activities of people ageing with an ID. Poor physical health was also identified as a predictor of preclusion from engagement across all three domains of self-care, productivity and leisure activities. Older age (65 years and older), having severe/profound level of ID and living in a residential setting were also found to be predictors of preclusion from engagement in two out of three domains of activity examined in this study. Implications: Occupational therapy has an important role to play in creation of environments that enable people with ID to engage in daily life, through working with individuals, families, service providers and local authorities to support creation of environments that facilitate engagement in daily life and ageing in place. Future studies would benefit from consideration of engagement in meaningful daily activities with greater depth with a focus on spiritual, cultural and institutional factors that influence engagement in daily life activities. As a component of health and well-being, greater consideration of engagement in daily activities is needed in research, policy and practice with people ageing with an intellectual disability.
APPROVED